2021
DOI: 10.1002/cbdv.202100594
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Isolation, Synthesis and Biological Evaluation of Terrein

Abstract: Terrein is a small-molecule polyketide compound with a simple structure mainly isolated from fungi. Since its discovery in 1935, many scholars have conducted a series of research on its structure identification, isolation source, production increase, synthesis and biological activity. Studies have shown that terrein has a variety of biological activities, not only can inhibit melanin production and epidermal hyperplasia, but also has anti-cancer, anti-inflammatory, anti-angiopoietic secretion, antibacterial, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Upon close inspection of ALT_1267 and the BGC it belonged to, however, we realized that the BGC was in fact reported recently as the terrein ( 4 ) BGC and is produced by various fungal species . However, its BGC was identified only in the A. terreus genome in 2014 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon close inspection of ALT_1267 and the BGC it belonged to, however, we realized that the BGC was in fact reported recently as the terrein ( 4 ) BGC and is produced by various fungal species . However, its BGC was identified only in the A. terreus genome in 2014 .…”
Section: Resultsmentioning
confidence: 99%
“…26 4 is a five-membered cyclic compound originally isolated from A. terreus 87 years ago 27 and is produced by various fungal species. 28 However, its BGC was identified only in the A. terreus genome in 2014. 29 Hence, we named ALT_1267 alterA and assigned the deduced functions of the open reading frames found in the BGC by sequence homology (Figure 2c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In order to confirm the absolute configuration at the C-7 position, two possible absolute configurations of 1 and 2 ((7R)-1, (7S)-1, (7R)-2, and (7S)-2), were used for NMR chemical shifts from quantum chemical computation at the B3LYP/6-311+G (d, p) level at the gas phase. The 1 H/ 13 C NMR chemical shift calculations and DP4+ probability analysis of 1 showed that the configuration of (7S)-1 was more likely than (7R)-1 (99.41% vs 0.59%) (Table S1), and the configuration of (7R)-2 was also more likely than (7S)-2 (99.31% vs 0.69%) (Table S2), respectively. Thus, the absolute configurations for 1 and 2 were assigned as 2R,3S,7S and 2R,3S,7R, given the name as pergilether A and aspergilether B, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Microbes are able to produce diverse and functional secondary metabolites, and these metabolites have provided plenty of chemical entities for the development of agrochemicals. Endophytic fungi represent an incredibly rich reservoir of biologically active secondary metabolites as a consequence of environmental adaptation, such as antifungal polyketides and alkaloids and insecticidal meroterpenes. , Butenolides, mainly isolated from the fungus Aspergillus terreus , have been reported to exhibit a wide array of biological activities, including antimalarial, antitubercular, antiviral, and β-glucuronidase inhibitory activities. Terreins, first separated from Aspergillus terreus Thom in 1935, were a series of stereoisomers containing the structure of cyclopentenone . Studies have shown that terreins had a variety of activities in many biological tests, including melanogenesis inhibitor, anticancer, anti-inflammatory, antiangiopoietic secretion, antioxidant, antiproliferative, antimicrobial, insecticidal activities, etc., and thus have potential application prospects in agriculture, medicine, beauty, and other fields. , …”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, chemical synthesis routes are followed by many drawbacks, like low yield, drastic reaction conditions, nonstereoselectivity, costly reagents, and a predominance of racemic products. 11,19,20 Terrein chemosynthesis was initiated in 1974, and later a “9-step approach” model was published. 21,22 However, the investigational support for this 9-step approach model has been deficient, and the biosynthesis of terrein has also remained mysterious.…”
Section: Introductionmentioning
confidence: 99%